Efektivitas Flipped Classroom Diintegrasikan Model Creative Problem Solving Terhadap Kemampuan Numerasi Siswa SMA - Merry Christina; Hepsi Nindiasari (Peneliti.net, 2022)
The purpose of this study is to measure whether there is a difference in the average numeracy ability of students who use flipped classroom learning integrated creative problem solving with creative problem solving models. This type of research uses a pure experiment with a pretest posttest control group design. The sample in this study were students of class XI IPA 2 as the experimental class and XI IPA 4 as the control class. The results of the study concluded that there was a difference in the average numeracy ability of the two groups which was supported by the higher average value of the experimental class than the control class.